2022
DOI: 10.1021/acs.molpharmaceut.2c00108
|View full text |Cite
|
Sign up to set email alerts
|

Different Serum, Different Protein Corona! The Impact of the Serum Source on Cellular Targeting of Folic Acid-Modified Chitosan-Based Nanoparticles

Abstract: The nanoparticle (NP) protein corona represents an interface between biological components and NPs, dictating their cellular interaction and biological fate. To assess the success of cellular targeting, NPs modified with targeting ligands are incubated with target cells in serum-free culture medium or in the presence of fetal bovine serum (FBS). In the former, the role of the corona is overlooked, and in the latter, the effects of a corona that does not represent the one forming in humans nor the respective di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…In one study, researchers explored the effect of incubating NPs with disease-derived biofluids on the delivery of cancer therapies. Chitosan NPs were incubated in FBS, normal human sera, or sera from breast cancer patients to evaluate the in vitro uptake of folic acid (FA)-conjugated NPs by MCF-7 breast cancer cells [ 84 ]. Breast cancer-derived sera (BrCr) were employed to better represent in vivo patient treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, researchers explored the effect of incubating NPs with disease-derived biofluids on the delivery of cancer therapies. Chitosan NPs were incubated in FBS, normal human sera, or sera from breast cancer patients to evaluate the in vitro uptake of folic acid (FA)-conjugated NPs by MCF-7 breast cancer cells [ 84 ]. Breast cancer-derived sera (BrCr) were employed to better represent in vivo patient treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal bovine serum (FBS), a commonly used supplement for cell and tissue culture, has been used as a protein source to study protein corona effects, providing fundamental knowledge of the behavior of NPs in in vitro systems. , In the same direction, a study from our group, also using FBS, revealed that the protein corona formed on Rf-SPIONs mainly contained immune-responsive proteins and blood coagulation factors . Interestingly, other studies reported that NPs show different interactions with proteins when incubated in human serum (HS) as opposed to FBS. This could eventually lead to different cellular responses. , Therefore, it is meaningful to gather information on the protein corona formed in HS which more closely mimics the human-relevant biological environment and has more realistic implications for clinical translation.…”
Section: Introductionmentioning
confidence: 98%
“…The successful application of nanotherapeutics (at minimum) relies on very precise control of the nanomaterial’s physiochemical properties (size, shape and surface chemistry), both to ensure that the NP possesses the necessary size-dependent properties, and to make sure that the NP targets and distributes in the patient correctly. ,,, In addition to the synthetic challenge of preparing nanotheranostic agents with precise physiochemical properties, in vivo applications of metal nanoparticles are further complicated by the fact that the “synthetic identity” of the NP is distinct from the “biological identity” that the NP takes on as soon as it enters an organism. The biological identity of the particle encompasses all the physiological changes that occur (size, aggregation state, adsorption of biomolecules, etc.) when the NP is exposed to a biological environment. , The best known physiochemical transformation associated with the biological identity of a NP is the formation of the protein corona (PC), a strongly adsorbed shell of serum proteins that bind to the NP as soon as it enters the bloodstream. ,,, The composition of the protein corona is influenced by both the original physiochemical properties of the NP and the biological compartments that the NP enters. The job of a nanotherapeutic is therefore made more difficult by the fact that nanomaterials are changed by the biological fluids that they encounter.…”
Section: Introductionmentioning
confidence: 99%
“…The PC becomes the new biological identity of the NP, dictating (for better or worse) its interactions with its surroundings. ,,, The formation of the NP’s PC is driven by a variety of intermolecular interactions, including van der Waals forces, hydrogen bonding, electrostatic forces, and hydrophobic interactions. , The dominant intermolecular forces depend on the NP’s physiochemical characteristics (primarily size and surface chemistry), although electrostatic interactions are generally believed to be a major driving force. ,,,, Because of its pivotal role in determining the biological identities of engineered NPs, the formation of the PC has been extensively researched, both with respect to the binding strength of individual proteins (particularly albumin) ,, and with respect to the composition of the PC (particularly PCs resulting from whole serum). ,,, The vast majority of this research has focused on NPs with diameters (50–200 nm) significantly larger than those of the proteins with which they are interacting with. Traditionally, the protein corona is understood to form in two empirically defined layers: the tightly associated “hard” corona at the NP surface and the loosely associated “soft” corona, which forms above the hard corona. ,,, Recent research has revealed that the structure of the protein corona depends on the relative size of the AuNP compared to the size of the protein binding to the NP surface. ,, Piella et al studied the formation of albumin corona formation of citrate-capped AuNPs ranging in size from 3.5 to 150 nm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation